2011
DOI: 10.1093/cercor/bhr263
|View full text |Cite
|
Sign up to set email alerts
|

Mental Addition in Bilinguals: An fMRI Study of Task-Related and Performance-Related Activation

Abstract: Behavioral studies show that bilinguals are slower and less accurate when performing mental calculation in their nondominant (second; L2) language than in their dominant (first; L1) language. However, little is known about the neural correlates associated with the performance differences observed between bilinguals' 2 languages during arithmetic processing. To address the cortical activation differences between languages, the current study examined task-related and performance-related brain activation during m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Such correlation between simple calculus and the activation of motor areas was the reason that brought to the use of the mental subtraction in the present study, even if the main purpose was to use it as a control for jump ; the results showed a significant improvement of the SVJ heights after mental subtraction (Table 2 and 3). A possible explanation for this effect may be the reported activation of language areas while calculating in mother tongue (French in this case) [64] and of motor areas found during exact arithmetic [65]. Moreover, and contrary to tiáo (senseless verb for whoever is not a sinophone), arithmetic has a significance for all humans representing, much as movement and gestures, a particular form of communication [66].…”
Section: Discussionmentioning
confidence: 93%
“…Such correlation between simple calculus and the activation of motor areas was the reason that brought to the use of the mental subtraction in the present study, even if the main purpose was to use it as a control for jump ; the results showed a significant improvement of the SVJ heights after mental subtraction (Table 2 and 3). A possible explanation for this effect may be the reported activation of language areas while calculating in mother tongue (French in this case) [64] and of motor areas found during exact arithmetic [65]. Moreover, and contrary to tiáo (senseless verb for whoever is not a sinophone), arithmetic has a significance for all humans representing, much as movement and gestures, a particular form of communication [66].…”
Section: Discussionmentioning
confidence: 93%
“…The latter is even more pronounced in the case of Alzheimer’s disease, mild cognitive impairment or dementia, which are more prevalent in the ageing population [ 2 ]. Elderly individuals with the above-mentioned pathologies are also more susceptible to develop age related hearing loss, presbycusis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 2007 ) observed that performing complex calculations in first and second languages rely on a common activation network, but with higher activations during calculations in second language. This was interpreted as evidence for extra language processing needs in second language; potentially translation of input from second into first language (Lin et al, 2011 ). Taken together, these bilingual studies point toward an advantage for both retrieving arithmetic facts and computing complex arithmetic problems in the first language, i.e., the language in which most bilinguals learned to do arithmetic.…”
Section: Introductionmentioning
confidence: 99%